Simulation of the Effect of Soil Temperature on Earth - Air Heat Exchanger Behavior - Qasim, Hussam Hakeem; Alshara, Ahmed K.; Abood, Falah A. (Basrah Journal for Engineering Sciences, 2024)
Modern life makes energy, and the source of it is very important. This renewable energy comes from the Earth-Air Heat Exchanger (EAHE) in the soil employed as an air conditioning device for buildings in the climate conditions in Basrah city, south of Iraq. In the present study, the EAHE buried in the soil is simulated numerically using the finite volume method with a soft package. ANSYS: Fluent 2021/R2. A parametric analysis was carried out to determine the effect of three depths ( Z = 1, 2, and 3 m), taking into account the physical properties of the soil in the area under study, which is in the city of Basrah in southern Iraq, at longitude 47.749° and latitude 30.568°, as well as the data and time of 1/6/2023 at 12 p.m., the diameter of the pipe ( D = 7.62, 10.16, and 15.24 cm), and different velocities ( v = 0.5, 1, and 1.5 m/s). The results are presented as a temperature contour and a velocity contour for the performance of EAHE. The important results showed that when the depth of the buried pipe decreases, the temperature of the air outlet and heat exchanger increases; when the diameter decreases, the air outlet temperature from the EAHE and the soil temperature decrease; when the length of the pipe is about 30 m, after this length, the decrease in temperature is very small; and the maximum temperature difference of about 10 °C between the ambient temperature and the outlet temperature of the EAHE was obtained at a depth of 3 m and a velocity of 1 m/s at a diameter of 7.62 cm.